India government and politics in a developing nation - Hardgrave, Robert L. (Thomson/Wadsworth, 2008)
Discusses India's political and economic development, its experiences with democracy, its foreign policy, and its institutional structure, within a historical and cultural context. This title includes coverage of elections and governmental changes, as well as coverage of India's growth as an economic market.